Looking across Takotna Valley from hill west of Takotna, Alaska, September 1914 - University of Washington Libraries. Special Collections Division.
Dotted line drawn on photo shows route. Caption under photo: Tacotna Valley from hill west of Tacotna. McPherson number: K488 PH Coll 495.2-52c Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.